Exploring the relationship between materialism, consumer ethnocentrism, and compulsive buying - Štefko, Róbert; Rigelský, Martin; Ondrijová, Ivana; Kráľová, Lenka (Frontiers in Psychology, 2025)
Materialistic values, consumer ethnocentrism, and compulsive buying represent three significant concepts in the field of consumer behavior. Theoretical models suggest that materialism may contribute to impulsive and compulsive purchasing behavior, while consumer ethnocentrism influences preferences for domestic products and attitudes toward foreign goods. The interconnection between these three constructs has been only marginally explored, especially in smaller Central European markets such as Slovakia, where cultural and socio-economic factors may shape consumer value orientations differently. The aim of this study was to analyze the relationships between materialistic values, consumer ethnocentrism, and compulsive buying among a sample of Slovak respondents. The research was based on data collected by the agency FOCUS through an online panel using quota sampling to ensure representativeness by demographic characteristics. The study also investigates whether ethnocentrism acts as a mediator between materialism and compulsive buying. Data was collected through an online questionnaire containing validated scales: the Material Values Scale, the Consumer Ethnocentrism Scale, and the Compulsive Buying Scale. To analyze the relationships between the variables, correlation analyses, linear regression, and mediation analysis using bootstrapping were employed. The results show that higher levels of materialism are statistically significantly associated with higher levels of compulsive buying. Ethnocentrism positively correlates with materialism but does not exhibit a direct relationship with compulsive buying. The mediating role of ethnocentrism between materialism and compulsive buying was not confirmed. The findings support theoretical assumptions about the influence of value orientations on problematic purchasing behavior. The study’s originality lies in integrating value-based and socio-cultural factors into a unified analytical model verified in the Slovak post-socialist context. From a theoretical perspective, the findings contribute to understanding how value orientations shape consumer behavior, while from a practical viewpoint, they provide implications for marketing strategies aimed at promoting responsible consumption and identifying risk groups prone to compulsive buying.